SEXUALITY AND DIVERSITY: : ANALYSIS OF DISCURSIVE USES IN THE CONSTRUCTION OF EDUCATIONAL POLICY, JUJUY-ARGENTINA - Julian, Ingrid Yamila; Guzman, Vilma Rosana; Da Silva , Kenia Lara (Revista Gênero e Interdisciplinaridade, 2021)
The article is based on an analysis carried out on the advances made in the Argentine State in terms of rights, with regard to Integral Sexual Education and the LGTBIM and women's movements. However, and based on this recognition, in terms of policy development in the educational field, questions that guide this document are raised, with the aim of contributing, not only to a discussion related to the educational and social processes through which sexuality passes, but also the historicity of gender relations and the ways in which sexual differences are symbolized. Directing the look on discursive uses as devices of power and subordination. For this, the document invites us to think about diversity from a context, characterized by a large presence of an ethnic population, with deeply rooted cultural traditions. On these bases, problematize the homogenizing social trend, which tries to impregnate this culture in corporeality and symbolism, calling into question social groups and, in particular, the nature of this diversity. Then, there is an outcome on Integral Sexual Education in the province of Jujuy-Argentina and the discursive uses that were included in the pedagogical processes. On the other hand, it refers to policies built under the aegis of diversity rights and, in particular, sexual diversity. Finally, to establish that the discussion undertaken here stems from the concern of members of two research teams, the Sociocultural Diversity in Regional Contexts Research Unit (UNIDISO, FHyCS-UNJu, Jujuy-Argentina) and the Center for Studies and Research on Teaching and Nursing Practice (NUPEPE, EE-UFMG, Belo Horizonte-Brazil), whose area of ​​development in the field of research is linked to Public Health, in this context, Integral Sexual Education and Sexual and Reproductive Health.